Tax Spillovers from US Corporate Income Tax Reform - Beer, Sebastian (IMF Working Papers; Working Paper, 2018)
This paper describes, and where possible tentatively quantifies, likely tax spillovers from the U.S. corporate income tax reform that was part of the broader 2017 tax reform. It calculates effective tax rates under various assumptions, showing among other findings, how the interest limitation and the Foreign Derived Intangible Income provision can raise or reduce rates. It tentatively estimates that under constant policies elsewhere, the rate cut will reduce tax revenue from multinationals in other countries by on average 1.6 to 5.2 percent. If other countries react in line with historical reaction functions, the revenue loss from multinationals rises to an average of 4.5 to 13.5 percent. The paper also discusses profit-shifting, real location, and policy reactions from the more complex features of the reform.